Peculiarities of Isolation, Cryopreservation and Allogeneic Transplantation of Rabbit’s Hepatocytes - Lebedinsky, A. S.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of introduction rate of hepatocyte suspension into a portal vein on transaminase activity in blood and liver morphology was studied. The obtained results have demonstrated, that the rate decrease of hepatocyte introduction when transplanting into a portal vein results in an even distribution of donor’s hepatocytes to recipient’s liver, allowing to reduce the thrombogenesis in the portal blood flow system and to decrease the damage degree for recipient’s own liver. The results can be used for studying the effect of transplanted cryopreserved hepatocytes at experimental pathologies of rabbit’s liver.